Brain Hypoxia and Ischemia - Yu, Shan Ping (Springer, 2017)
Brain Hypoxia and Ischemia explores the various aspects of cell death and survival that are crucial for understanding the basic mechanisms underlying brain hypoxia and ischemia. Chapters focus on a panorama of issues including the role of ion channels/transporters, mitochondria and apoptotic mechanisms, the roles of glutamate/NMDA, mechanisms in penumbral cells and the importance of intermittent hypoxia and gene regulation under these stressful conditions. The volume explores findings from both mammalian and invertebrate model systems and their applicability to human systems and diseases. Careful consideration is also given to differences in hypoxia and ischemia across development.